The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s12975-020-00788-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle Factors on Cognitive Resilience: Commentary on “What This Sunny, Religious Town in California Teaches Us About Living Longer”

Abstract: Recent media reporting on healthy living and longevity highlights the ever-increasing public interest on the effects of lifestyle choices on disease risk. The recent CNN article "What this sunny, religious town in California teaches us about living longer" by LaMotte and previous media reports have featured stories about the city of Loma Linda in California, one of the five original "blue zones" in the world, areas or populations with documented high longevity. Loma Linda was labeled as a "blue zone" based upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A cohort study of Taiwanese vegetarians and vegans in midlife who do not consume seafood revealed lower risk of dementia or cognitive decline compared with nonvegetarians despite having low n-3 PUFA blood levels [19]. Among those living in the World Health Organization designated Blue Zones [20], such as the Seventh-day Adventist community residing in Loma Linda California, consumption of a plant-based diet that excludes red meat, chicken, or seafood is associated with lower levels of both cardiovascular and neurodegenerative diseases such as AD [21]. When compared to individuals that consume meat, vegans show lower levels of xanthine, histidine, branched fatty acids, acetylated peptides, ceramides, and long-chain acylcarnitines, among other metabolites [22].…”
Section: Vegetarians and Vegans With Healthy And Diverse Microbiota C...mentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study of Taiwanese vegetarians and vegans in midlife who do not consume seafood revealed lower risk of dementia or cognitive decline compared with nonvegetarians despite having low n-3 PUFA blood levels [19]. Among those living in the World Health Organization designated Blue Zones [20], such as the Seventh-day Adventist community residing in Loma Linda California, consumption of a plant-based diet that excludes red meat, chicken, or seafood is associated with lower levels of both cardiovascular and neurodegenerative diseases such as AD [21]. When compared to individuals that consume meat, vegans show lower levels of xanthine, histidine, branched fatty acids, acetylated peptides, ceramides, and long-chain acylcarnitines, among other metabolites [22].…”
Section: Vegetarians and Vegans With Healthy And Diverse Microbiota C...mentioning
confidence: 99%
“…plant-based diet that excludes red meat, chicken, or seafood is associated with lower levels of both cardiovascular and neurodegenerative diseases such as AD [21]. When compared to individuals that consume meat, vegans show lower levels of xanthine, histidine, branched fatty acids, acetylated peptides, ceramides, and long-chain acylcarnitines, among other metabolites [22].…”
Section: Key Pointsmentioning
confidence: 99%
“…LLUH is a Seventh-day Adventist institution that as part of its mission to ‘Keep Man Whole’ promotes specific faith-based principles of healthy lifestyle and disease prevention in its healthcare, academic teaching, administration and campus and hospital environment 2 3. These include avoidance of tobacco and alcohol, and adherence to a plant-based diet pattern that encourages consumption of specific plant foods (ie, legumes, nuts) in place of animal products 2.…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…While a low ω-3 index score or fish consumption are risk factors for dementia, the risk conferred by a low ω-3 index score might be offset by other factors. For example, in the Adventist population, 1 of the 5 original “blue zones” ( 9 ) in the world with a high level of education, healthy lifestyles, and high longevity, many individuals follow a predominantly vegetarian dietary pattern that excludes fish consumption ( 10 ) and, presumably, they have low ω-3 index scores. Vegetarians who do not consume fish did not perform worse on cognitive measures compared with matched controls who consumed fish ( 11 ).…”
mentioning
confidence: 99%